ENTERPRISE RISK MANAGEMENT AND BOARD EXPERTISE OF BANKS IN NIGERIA (Journal of Contemporary Issues in Accounting, 2023)
This study investigated the association between Enterprise risk management and board expertise of banks in Nigeria, spanning from 2011 to 2020 financial years. The objective was to ascertain the degree of board expertise as an attribute of the board to determine efficiency in enterprise risk management. Ex post facto research design was used while panel data was collected through the means of content analysis from the financial statements of the seven banks chosen using judgemental sampling technique. Data generated was analysed using descriptive statistics, correlation and panel regression analysis. Fixed effect result was used in making inferences as specified by the outcome of Hausman test. The result indicates that board expertise has statistical significant effect on enterprise risk management at 5% level wherein it recommends that adequate board members with account and finance knowledge should be included in board appointments for better corporate risk administration.
Keywords: Enterprise Risk Management; Board Expertise; Risk Appetite